Inflation perceptions and expectations in the euro area: the role of news - Cristian Badarinza; Marco Buchmann (European Central Bank (ECB), 2009)
The aim of this study is to assess empirically to what extent the degree of heterogeneity of consumers' inflation perceptions and expectations is driven by the flow of information related to current and future price developments in the euro area. We conduct the analysis both on an aggregate level for the euro area as well as for a set of countries using panel techniques. We find that the degree to which consumers' expectations are discordant is negatively related to news intensity. Moreover, the results suggest that the absolute bias in expectations decreases as news become more intense and this effect has become more pronounced since the introduction of the common currency.
Keywords: D12; D84; E31; 330; euro area; heterogeneity; inflation expectations; news; survey data; Inflationserwartung; Preisniveau; Ankündigungseffekt; Aggregation; Panel; Eurozone; EU-Staaten